Politikai stratégiák, avagy a horvát választási rendszer változásai - Lőrinczné Bencze, Edit (Közép-Európai Közlemények, 2017)
In the independent Croatia elections are among the most important political processes, hence they are the central elements of the whole transition. The importance of elections has increased the importance of electoral systems as institutional forms of arranging elections, and they became main constitutional arrangements of the new democratic country. There have been no any new democracies in Central and Eastern Europe with such frequent and radical changes of electoral systems in the first decade after political changes. In the entire transitional region there has been no country that in ten years carried out three big, electoral reforms. In ten years, all the central models of the electoral systems for the first chamber of the Parliament have been remoulded: the absolute majority system (1990), the segmented system with the equal ratio of direct and closed list seats (1992), the segmented system with the preponderant share of the closed list seats (1995) and the proportional representation (2000).